2022
DOI: 10.1007/s10040-022-02513-5
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating drought and water scarcity in the Mediterranean region through managed aquifer recharge

Abstract: Drought and water scarcity can significantly impair the sustainable development of groundwater resources, a scenario commonly found in aquifers in the Mediterranean region. Water management measures to address these drivers of groundwater depletion are highly relevant, especially considering the increasing severity of droughts under climate change. This study evaluates the potential of managed aquifer recharge (MAR) to offset the adverse effects of drought and water scarcity on groundwater storage. Los Arenale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…The few stations showing an increasing trend of groundwater depth (i.e., lower storage) are mainly located over the Southern agricultural area (shown in the focus provided in Figure 10d), thus suggesting that human‐induced interventions may be the reason for opposite trends with respect to the overall behaviour. A similar result has been recently obtained in a study carried out in central Spain (Henao Casas et al, 2022); Peña‐Arancibia et al (2020) highlighted the combined effects of reduced rainfall and agricultural water use on groundwater depletion in Bangladesh, suggesting an approach based on complementary strategies for facing the issue.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The few stations showing an increasing trend of groundwater depth (i.e., lower storage) are mainly located over the Southern agricultural area (shown in the focus provided in Figure 10d), thus suggesting that human‐induced interventions may be the reason for opposite trends with respect to the overall behaviour. A similar result has been recently obtained in a study carried out in central Spain (Henao Casas et al, 2022); Peña‐Arancibia et al (2020) highlighted the combined effects of reduced rainfall and agricultural water use on groundwater depletion in Bangladesh, suggesting an approach based on complementary strategies for facing the issue.…”
Section: Discussionsupporting
confidence: 82%
“…Ouassanouan et al (2022) observed decreasing trends of groundwater availability in the Tensift watershed (Morocco) during the period 1973–2021, exacerbated by the combined effects of climatic alterations and of increasing agricultural water demand. Finally, Henao Casas et al (2022) analysed levels referring to two groundwater bodies located within the Douro river basin, in Spain, during the time span 2001–2020. The authors found increasing storage trends at monitoring sites falling within areas where specific recharge strategies are adopted and opposite results elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…There is a spatial and temporal correlation between MAR and increasing groundwater level trends in LA. Our results align with the analysis by Henao Casas et al, 2022), showing the adequacy of this technology to cope with drought, which is especially visible in the groundwater level analyses of the last period (2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). Water management measures implemented on a national and regional scale, including plans for the modernisation of irrigation, and programs to quantify groundwater abstractions (e.g., ALBERCA), have had a limited impact on the study area, at least to the depth of our analysis.…”
Section: Managed Aquifer Recharge and Outlooksupporting
confidence: 91%
“…Several studies have explored the effect of the MAR sites on Los Arenales Aquifer. These studies have focused on hydrogeological (CONAMA, 2019), socioeconomic (Fernández-Escalante et al, 2016, governance (Fernández-Escalante and López-Gunn, 2021), climate change (Fernández-Escalante et al, 2019b;Henao Casas et al, 2022), andtechnical (Fernández-Escalante andPrieto Leache, 2013;Fernández-Escalante and San Sebastian Sauto, 2019a;MARSOL, 2015) aspects. However, none of them has analysed the evolution of groundwater levels and water use dynamics on a regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, intensive groundwater use led to the degradation of numerous springs and wetlands (Llorente & Bejarano, 2018). To counter these effects, the Douro basin authority has implemented various corrective measures, including artificial recharge (Henao Casas, Fernández Escalante, & Ayuga, 2022; Henao Casas, Fernández‐Escalante, & Ayuga, 2022; Henao Casas, Fernández‐Escalante, Calero Gil, & Ayuga, 2022; Mayor, de la Hera‐Portillo, et al, 2021; Mayor, López Gunn, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%